2019
DOI: 10.1021/acsami.9b06933
|View full text |Cite
|
Sign up to set email alerts
|

Simple Is Best: A p-Phenylene Bridging Methoxydiphenylamine-Substituted Carbazole Hole Transporter for High-Performance Perovskite Solar Cells

Abstract: Methoxydiphenylamine-substituted carbazole (MODPACz) is widely used to construct hole-transporting materials (HTMs) for perovskite solar cells (PSCs), whose performances rely highly on the linking way of the MODPACz units and the simplicity of the π-bridge. In this paper, we report a new HTM, pPh-2MODPACz, using one of the simplest πbridges p-phenylene to link the MODPACz units. The structural feature endows pPh-2MODPACz with high hole mobility and conductivity, efficient hole extraction ability, and good film… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 37 publications
0
37
0
Order By: Relevance
“…Several of the structures, irrespective of the device architecture, show reasonable performance and equivalent hole mobilities of the order 10 −3 cm 2 V −1 s −1 , which is on the higher range of typical polymeric HTMs (10 −3 –10 −5 cm 2 V −1 s −1 ). Interestingly, it should be noted exceptional examples included PTEG (16.4 × 10 −4 cm 2 V −1 s −1 ), P1 (17.2 × 10 −4 cm 2 V −1 s −1 ), M118 (17.5 × 10 −4 cm 2 V −1 s −1 ), pBBTa‐BDT2 (20 × 10 −4 cm 2 V −1 s −1 ), RCP (30.9 × 10 −4 cm 2 V −1 s −1 ), and R1 (37 × 10 −4 cm 2 V −1 s −1 ) . Structural observations showed that few were purely of a nitrogen heterocyclic nature, i.e., M118, with several of the more exceptional performances containing thiophene, i.e., pBBTa‐BDT2, and several with extended conjugation and polymeric backbones, i.e., R1, PTEG, and RCP, which showed enhanced performance over small molecular and larger branched molecular structures.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Several of the structures, irrespective of the device architecture, show reasonable performance and equivalent hole mobilities of the order 10 −3 cm 2 V −1 s −1 , which is on the higher range of typical polymeric HTMs (10 −3 –10 −5 cm 2 V −1 s −1 ). Interestingly, it should be noted exceptional examples included PTEG (16.4 × 10 −4 cm 2 V −1 s −1 ), P1 (17.2 × 10 −4 cm 2 V −1 s −1 ), M118 (17.5 × 10 −4 cm 2 V −1 s −1 ), pBBTa‐BDT2 (20 × 10 −4 cm 2 V −1 s −1 ), RCP (30.9 × 10 −4 cm 2 V −1 s −1 ), and R1 (37 × 10 −4 cm 2 V −1 s −1 ) . Structural observations showed that few were purely of a nitrogen heterocyclic nature, i.e., M118, with several of the more exceptional performances containing thiophene, i.e., pBBTa‐BDT2, and several with extended conjugation and polymeric backbones, i.e., R1, PTEG, and RCP, which showed enhanced performance over small molecular and larger branched molecular structures.…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly, it should be noted exceptional examples included PTEG (16.4 × 10 −4 cm 2 V −1 s −1 ), [87] P1 (17.2 × 10 −4 cm 2 V −1 s −1 ), [85] M118 (17.5 × 10 −4 cm 2 V −1 s −1 ), [84] pBBTa-BDT2 (20 × 10 −4 cm 2 V −1 s −1 ), [4] RCP (30.9 × 10 −4 cm 2 V −1 s −1 ), [77] and R1 (37 × 10 −4 cm 2 V −1 s −1 ) . [131] Structural observations showed that few were purely of a nitrogen heterocyclic nature, i.e., M118, with several of the more exceptional performances containing thiophene, i.e., pBBTa-BDT2, and several with extended conjugation and polymeric backbones, i.e., R1, PTEG, and RCP, which showed enhanced performance over small molecular and larger branched molecular structures. This indicates that high hole mobility (10 −1 -10 −2 cm 2 V −1 s −1 ) in dopant free HTMs may not be as critical as achieving optimum structures that extend conjugation with functional groups that enable better interaction between device layers.…”
Section: Molecular Engineering Of Novel Organic Hole Transporting Matmentioning
confidence: 99%
See 1 more Smart Citation
“…The 2,6PyDANCBZ and 3,5PyDANCBZ exhibit a high glass transition temperature (Tg) of 132 and 126 °C, respectively, which are higher than that of Spiro-OMeTAD. 48 The notable high Tg shown by HTMs will prevent any phase change process, suggesting the functioning of devices in the temperature window required for commercial validation. calculated from the slope of the J 1/2 -V curves ( Figure S3) according to Mott-Gurney law (J=9εε0µVapp 2 /8L 3 ) and the data were collected in Table 1.…”
Section: Opto-electrical Thermal Semiconducting and Photovoltaic Prmentioning
confidence: 99%
“…Low‐cost methoxydiphenylamine‐substituted carbazole (MODPACz) is mostly used at the peripheral of HTMs for PSCs, whose performances highly rely on the linking way of the MODPACz units. [ 42 ] The simplest way is to connect by phenyl bridge, and the molecules based on this configuration demonstrate reasonable hole mobility and conductivity, feasible synthesis, and good film‐forming capability, all leading to a PCE over 20% in PSCs with MAPbI 3 and planar device structure. Because of good conductivity, these HTMs showed a high PCE of 16.07% in devices without adding HTM, which is much better than the devices with the classical spiro‐OMeTAD.…”
Section: Chemically Doped Hole Transporting Materialsmentioning
confidence: 99%